STUDY OF ECOLINGUISTIC ASPECTS OF NEOLOGISMS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
The article raises the issues of neology and ecolinguistics. The authors specify the criteria of ecolinguistic approach to studying neologisms based on ecolinguistic monitoring which helps to elicit factors that influence the formation of new words, spheres in which they function in language as well as to define the type of new words and number of loanwords among them.